Electrochemically induced amorphization and unique lithium and sodium storage pathways in FeSbO4 nanocrystals - Edison, Eldho (2020)
The increasing energy demands have prompted research on conversion and alloying materials, offering high lithium and sodium storage capacities. However, most of these materials suffer from huge volume expansion and degradation over the thousands of charging and discharging cycles required for commercial applications. In this study, we demonstrate a facile route to synthesize FeSbO4 nanocrystals that possess theoretical lithium and sodium storage capacity of 1220 mAh g–1. Operando X-ray diffraction studies reveal the electrochemically induced amorphization of the nanocrystals upon alkali-ion storage. We achieved specific storage capacities of ∼600 mAh g–1 for lithium and ∼300 mAh g–1 for sodium, respectively. The disparity in the lithium and sodium electrochemistry arises from the unique lithiation/sodiation pathways adopted by the nanocrystals. This study offers new insights into the chemistry and mechanism of conversion- and alloying-based energy storage materials that would greatly assist the development of next-generation active materials for energy storage.